Ø£ÙˆØ¬Ù‡ Ø§Ù„Ø§Ø®ØªÙ„Ø§Ù Ø¨ÙŠÙ† Ø§Ù„Ø³ÙŠØ±ØªÙŠÙ† Ø§Ù„Ø°Ø§ØªÙŠØªÙŠÙ† (Ø§Ù„Ø£ÙŠØ§Ù… Ù„Ø·Ù‡ ØØ³ÙŠÙ† ÙˆØ£ÙƒÙ‰ Ù„ÙˆÙˆÙ„Ù‰ Ø´ÙˆÙŠÙ†ÙƒØ§) AWJUH AL-IKHTILAF BAINA AS-SIRATAIN ADZ-DZATITAIN (AL-AYYAM LI TAHA HUSSEIN WA AKE LI WOLE SOYINKA) - Zubair, Abdulhakeem (UIN Maulana Malik Ibrahim Malang, 2020)
Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ù‚Ø§Ø±Ù†Ø© Ù‡ÙŠ ÙÙ† Ù…Ù† ÙÙ†ÙˆÙ† Ø§Ù„Ø£Ø¯Ø¨ Ø§Ù„ØªÙŠ ØªØ¹Ø²Ø² ØªÙ„Ø§Ù‚ÙŠ Ø§Ù„Ø£ÙÙƒØ§Ø± ÙˆØ§Ù„Ù…Ø¹Ø±ÙØ© ÙˆØ§Ù„Ø«Ù‚Ø§ÙØ©. ÙˆÙ„Ù‚Ø¯ ØªÙ„Ù‚Ù‰ Ù‡Ø°Ø§ Ø§Ù„Ù†ÙˆØ¹ Ù…Ù† Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù†Ø§ÙŠØ© ÙØ§Ø¦Ù‚Ø© Ù„Ø¯Ù‰ Ø§Ù„Ø¯Ø§Ø±Ø³ÙŠÙ† ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„Ø¥Ù†Ø¬Ù„ÙŠØ²ÙŠØ© ÙÙŠ Ø§Ù„Ø¹ØµØ± Ø§Ù„ØØ¯ÙŠØ«. ÙˆÙ…Ø¹ Ø°Ù„ÙƒØŒ ÙƒØ§Ù†Øª Ù…Ù‚Ø§Ø±Ù†Ø© Ø§Ù„Ø¹Ù…Ù„ Ø§Ù„Ø£Ø¯Ø¨ÙŠ Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø¨Ø§Ù„Ø¹Ù…Ù„ Ø§Ù„Ø£Ø¯Ø¨ÙŠ Ø§Ù„Ø¥Ù†Ø¬Ù„ÙŠØ²ÙŠ Ù†Ø§Ø¯Ø±Ù‹Ø§ Ø¬Ø¯Ù‹Ø§ ÙÙŠ Ù…Ø¬Ø§Ù„ Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù†ÙŠØ¬ÙŠØ±ÙŠØ§. Ù„Ø°Ù„Ùƒ Ø±ÙƒÙ‘Ø²ØªÙ Ù‡Ø°Ù‡ Ø§Ù„ÙˆØ±Ù‚Ø© Ø¹Ù„Ù‰ Ø§Ø³ØªÙ†Ø¨Ø§Ø· ÙˆØ¯Ø±Ø§Ø³Ø© Ø£ÙˆØ¬Ù‡ Ø§Ù„Ø§Ø®ØªÙ„Ø§Ù Ø¨ÙŠÙ† ÙƒØªØ§Ø¨ÙŠ Â«Ø§Ù„Ø£ÙŠØ§Ù…Â» Ù„Ø·Ù‡ ØØ³ÙŠÙ† ÙˆÂ«Ø£ÙƒÙ‰ Ø³Ù†ÙˆØ§Øª Ø§Ù„Ø·ÙÙˆÙ„Ø©Â»Ù„Ù€ Wole Soyinka (ÙˆÙˆÙ„ÙŠ Ø´ÙˆÙŠÙ†ÙƒØ§). ÙˆÙ…Ù† Ø£Ù‡Ø¯Ø§ÙÙ‡Ø§ Ø£Ù† ØªÙ‚ÙˆÙ… Ø¨Ù…Ù‚Ø§Ø±Ù†Ø© ÙˆØªØ¨Ø§ÙŠÙ† Ù…Ø¶Ø§Ù…ÙŠÙ† Ø§Ù„Ø¹Ù…Ù„ÙŠÙ† Ø§Ù„Ø£Ø¯Ø¨ÙŠÙ’ÙŠÙ†ØŒ ÙˆØªØÙ„ÙŠÙ„ Ø§Ù„Ø¬Ø§Ù†Ø¨ Ø§Ù„ÙÙ†ÙŠ ÙˆØ§Ù„Ø³Ø±Ø¯ÙŠ ÙÙŠ Ø§Ù„ÙƒØªØ§Ø¨ÙŠÙ† Ø§Ù„Ù…Ù‚Ø§Ø±Ù†ÙŠÙ† ÙˆØªÙˆØ¶ÙŠØ Ø¨Ø¹Ø¶ Ø³Ù„ÙˆÙƒ Ø§Ù„Ø·ÙÙˆÙ„Ø© Ø¹Ù„Ù‰ Ø§Ù„Ø±ØºÙ… Ù…Ù† Ø®Ù„ÙÙŠØ© Ù…Ù†Ø·Ù‚ØªÙŠÙ‡Ù…Ø§ ÙˆØ£ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠØªÙŠÙ‡Ù…Ø§ ÙˆØ¯ÙŠÙ†ÙŠÙ‡Ù…Ø§ Ø§Ù„Ù…Ø®ØªÙ„ÙÙŠÙ†Ø› ÙˆØ§Ø¹ØªÙ…Ø¯Øª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù„Ù‰ Ù…Ù†Ù‡Ø¬ÙŠÙ† Ø£Ø³Ø§Ø³ÙŠ ÙŠÙ†Ù‡Ù…Ø§ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠ ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠØ› Ø£Ù…Ø§ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠ ÙÙŠØªÙ†Ø§ÙˆÙ„ Ù†Ø¨Ø°Ø© ÙŠØ³ÙŠØ±Ø© Ø¹Ù† ØÙŠØ§Ø© ÙƒÙ„ Ù…Ù† Ø§Ù„Ø£Ø¯ÙŠØ¨ÙŠÙ† Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ø¯Ø±Ø§Ø³Ø©. ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠ Ø¹Ø¨Ø§Ø±Ø© Ø¹Ù† Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ø³ÙŠØ±ØªÙŠÙ† Ø§Ù„Ø°Ø§ØªÙŠØªÙŠÙ† Ù„Ù„Ø£Ø¯ÙŠØ¨ÙŠÙ†ØŒ ÙˆØªÙ…Ù‘ ØªØÙ„ÙŠÙ„Ù‡Ù…Ø§ Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø¹Ø§ÙŠÙŠØ± Ø§Ù„Ø£Ø¯Ø¨ÙŠØ© ÙˆØ§Ù„ÙÙ†ÙŠØ©. ÙˆÙÙŠ Ø§Ù„Ø®ØªØ§Ù… Ø£Ø«Ø¨Øª Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø£Ù†Ù‘ Ø§Ù„Ø³ÙŠØ±ØªÙŠÙ† ØªØ¹ÙƒØ³Ø§Ù† ØÙŠØ§Ø© Ø§Ù„Ø·ÙÙˆÙ„Ø© Ù„Ù„Ú©Ø§ØªØ¨ÙŠÙ† Ù…Ø¹ Ø§Ù„Ø§Ø®ØªÙ„Ø§Ù ÙÙŠ Ø§Ù„Ø¨ÙŠØ¦Ø© ÙˆØ§Ù„Ø«Ù‚Ø§ÙØ©ØŒ ÙˆÙƒÙ„Ø§ Ø§Ù„Ø¹Ù…Ù„ÙŠÙ† ÙŠØªÙÙ‚ Ù…Ø¹ Ø§Ù„Ù…Ø¹Ø§ÙŠÙŠØ± Ø§Ù„ÙÙ†ÙŠØ© ÙˆØ§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù„ØºÙˆÙŠØ© Ø§Ù„Ù…ÙˆØ¶ÙˆØ¹Ø© ÙÙŠ ÙƒÙ„ØªÙŠ Ø§Ù„Ù„ØºØªÙŠÙ† Ù…Ø¹ Ø§Ø®ØªÙ„Ø§ÙÙ‡Ù…Ø§ ÙÙŠ Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ÙƒØªØ§Ø¨Ø©. ÙˆØ£ÙˆØµØª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù†ØªØªØ±Ø¬Ù… Ø£Ø¹Ù…Ø§Ù„ ÙˆÙˆÙ„ÙŠ Ø´ÙˆÙŠÙ†ÙƒØ§ Ø¥Ù„Ù‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ£Ø¹Ù…Ø§Ù„ Ø·Ù‡ ØØ³ÙŠÙ† Ø¥Ù„Ù‰ Ø§Ù„Ø¥Ù†Ø¬Ù„ÙŠØ²ÙŠØ© ÙƒÙ…Ø§ ØªØØ«Ù‘ Ø§Ù„Ø¨Ø§ØØ«ÙŠÙ† Ø£Ù† ÙŠØ±ÙƒÙ‘Ø²ÙˆØ§ Ø¹Ù†Ø§ÙŠØªÙ‡Ù… Ø¹Ù„Ù‰ ØªØ¬Ø§Ø±Ø¨ Ø§Ù„Ø·ÙÙˆÙ„Ø© ÙÙŠ Ø£Ø¹Ù…Ø§Ù„ Ø§Ù„Ø£Ø¯Ø¨Ø§Ø¡ Ø§Ù„Ø£ÙØ§Ø±Ù‚Ø© Ø±ØºÙ… Ø§Ø®ØªÙ„Ø§Ù Ø¨ÙŠØ¦Ø§ØªÙ‡Ù… ÙˆØ«Ù‚Ø§ÙØ§ØªÙ‡Ù…Ø› Ù„Ø§Ø³ØªÙ†Ø¨Ø§Ø· Ø§Ù„ÙÙˆØ§Ø¦Ø¯ ÙˆØ§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ù…Ù† ØªÙ„Ø§Ù‚ÙŠ Ø§Ù„Ø£ÙÙƒØ§Ø± ÙˆØ§Ù„Ù…Ø¹Ø§Ø±Ù.Comparative study is an art of literature promoting the convergence of ideas, knowledge and culture. This type of study has received great concern among students of Arabic and English in the modern era. However, the comparison between Arabic and English literary work is very rare in the field of Arabic studies in Nigeria. Therefore, this paper focuses on the differences between the books, â€œAl-Ayyamâ€ by Taha Hussein and â€œAke Years of Childhoodâ€ by Wole Soyinka. Its objectives were to compare and contrast the contents of the two literary works, to analyze the artistic and narrative side of them, and to clarify some childhood behaviours despite their different backgrounds in their regions, ideologies and religions. This study relied on two basic approaches, the historical and analytical methods. The historical method deals with a simple overview of the lives of both writers. The analytical method includes studying the writersâ€™ biographies analyzed based on literary and artistic criteria. In conclusion, the findings show that the two biographies reflect the writersâ€™ childhood with the difference in the environment and culture. Besides, both works are consistent with the technical standards and the linguistic rules established in both languages with their differences in writing style. The study recommended that Soyinkaâ€™s work is translated into Arabic and Husseinâ€™s work into English. Researchers should focus more on the works of African writers despite their different environment and cultures to derive benefits and information from the convergence of ideas and knowledge.